Information exposure and corporate citizenship - Liu, Lisa Yao,Lu, Shirley (Stigler Center for the Study of the Economy and the State, University of Chicago Booth School of Business, 2021)
We explore how information exposure, specifically information transmission within organizations, facilitates companies' roles as corporate citizens. We study whether US firms' business networks with China and Italy become their information advantage, and examine whether firms use relevant information to mitigate the negative shocks of COVID-19. We start by validating our measurement of information exposure. Next, we find that a higher number of work-from-home (
10419/262714
Keywords: Graue Literatur; Information exposure; information transmission; business networks; COVID; corporate citizenship